Television advertising television: measuring the ability of television promos to deliver ratings for new programs using single-source data. Issue 3 (4th May 2018) - Beal, Virginia; Romaniuk, Jenni; Sharp, Byron
ABSTRACT: The entertainment industry relies heavily on advertising to attract audiences. This article demonstrates a method to measure the effect of on-air television promotions, or promos, on viewing behaviour, based on a well-established single-source method for determining the causal impact of advertising on sales. We illustrate this method on 18 new prime-time programs, showing that promos have a positive impact on viewing behaviour. Exposed viewers are substantially more likely to view the premiere episode of a new series, across a wide range of different television-viewing weights, frequency of promo exposures and program types. The research also shows evidence of reach-based scheduling strategies being generally more efficacious than frequency-based strategies. These findings provide guidance to help networks implement their promo strategy more effectively, as well as a method for future research into the effectiveness of television promos as this approach can be utilized in any country with a television ratings panel.